Evaluation of Introduction to Academic Culture and Student Affairs (PBAK) UIN Antasari Banjarmasin - Mufidah, Nida; Noval, Muhammad; Kurdi, Musyarrafah Sulaiman; Fauzan, Muhammad Hendrie (Dinamika Ilmu, 2024)
This research aims to obtain information regarding participants' responses regarding the materials presented in Introduction to Academic Culture and Student Affairs (PBAK) activities. The subjects of this study were PBAK students batch 2018 and 2019, totaling 6198 students. Extracting data using questionnaires, observations, interviews, and documentation. The results of this study indicate that the implementation of PBAK batch 2018 and 2019 can be accepted by students which the materials mostly in positive responses, (1) correlate with the adjustment attitude of PBAK participant 98,37 % positive responses on history, vision and mission of UIN Antasari Banjarmasin, (2) there is 94, 56 % positive responses regarding the Islamic and national insight material, ( 3) participants also responded 97.33% positively to study success and organizations in Higher Education material, (4) social environmental responsibility is 96,86 % in positive response, (5) there are 96.57% students gave positive responses regarding the material on critical analysis of the implementation of the student government concept, (6) the total number of applicants expressed positive responses cosmopolitan millennials with morals and social care and transformation and agent of win manifesto towards civilized people were more about that 97.53% , (7) the material of intrapersonal and interpersonal skills material, it is known that 96.86% of gave positive responses to this material, (8) the scientific writing material was 96,01% in positive response and (9) For 96,61 % positive response given to students ethics material. The psychological impact felt by participants is the emergence of feelings of joy or happiness, usefulness, and motivation from participating in PBAK activities.